Efektivitas Instrumen Evaluasi Arjuna Terhadap Keterampilan Menulis Artikel Ilmiah Mahasiswa - Nur Shabrina Reznani (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2022)
This study aims to see the effectiveness of Arjuna's evaluation instrument on students' article writing skills. The research method used in this study was a pre-experiment with a research design of One Group Pretest-Posttest Design. The sample of this study amounted to 40 students. The data collection technique used a test technique which was divided into pretest and posttest. The data processing technique used a t-test calculation with the SPSS 20 program. The results showed that Arjuna's evaluation was effective on students' writing skills. The mean score on the initial test was 42.15, an increase of 14.02 to 56.17 on the final test. The t-test results show that tcount is 8.843 and ttable (df 62 = 1.669). The value of tcount (8.843) > ttable (1.669). The results show that Ho is rejected and Ha is accepted. Thus, it can be said that arjuna's evaluation has an influence on the ability to write scientific articles of Management students in Indonesian general courses.